Deming's total quality management movement and the Baskin Robbins problem - White, Orion F.; Wolf, James F. (1995)
"W. Edwards Deming's philosophy of total quality management (TQM) constitutes more than an approach to management. It is also a full-fledged theory of organization and a theory of society and politics that holds important implications for relations between nation-states in the emerging "new world order." When examined in this light, it appears that TQM is not collectivist or Marxist in the way that it is sometimes understood, but that it does stand in tension with a number of aspects of the traditional liberal American political and social tradition. At the same time, however, it is quite consistent with the revolutionary, antifederalist subtheme that has persisted throughout U.S. history"
Keywords: Management; Total quality management